I [pronounced as "Ka] [videorecording] - Ateneo Center for Social Policy and Public Affairs ([Quezon City] Ateneo Center for Social Policy and Public Affairs, 1992)
Retells the Philippine Revolution from the perspectives of the masses. It parallels early Katipunan's initiation rites with the 300 years struggle.
This was aired on RPN 9 on November, 1992.
Editor, Kedy Sanchez.
Keywords: Flores, John Marin; Estuar, Jose; Katipunan; Philippines -- History -- Revolution; Philippine -- History